Módulo para avaliação automática de programas para MOODLE - Bado, Alex (2015)
Courses in the Information Technology Area have a large number of disciplines related to programming, also, they have considerable amount of exercises related to development, which requires a lot of time and effort from the teacher correcting each work individually. Automatic corrector systems programs are an attempt to help the teacher in this process, creating a pattern for corrections. Automatic corrector programs have as main goal to provide feedback of the student’s activity after they upload the file with source code of their program without the need for the teacher to read their code to find possible errors. Considering this scenario, this work has as objective the development of a corrector program module for the virtual MOODLE environment, throughout the PHP language. For the correction to be possible the program must allow the entrance of values throughout the command line and, these values when submitted to the program execution must create a return that will be identified throughout the module. The teacher will feed defaut values for the income and outcome, which will be used as base for the correction. The plugin has a few more customizations to help the teacher. The results were satisfactory, because the process was streamlined, noting that this process should be extended with support for other languages.